Peripheral Inflammation and Cognitive Performance in Middle-Aged Adults With and Without Type 2 Diabetes: Results From the ENBIND Study - Dyer, Adam H.; McKenna, Louise; Batten, Isabella; Jones, Karen; Widdowson, Matthew; Dunne, Jean; Conlon, Niall; Reilly, Richard; Woods, Conor P.; O’Neill, Desmond; Gibney, James; Bourke, Nollaig M.; et al. (Frontiers in Aging Neuroscience, 2020)
Midlife Type 2 Diabetes Mellitus (T2DM) is associated with a greater risk of dementia in later life. Peripheral inflammation and its impact on cognition is proposed as one of the pathological mechanisms mediating this link. However, studies have primarily focused on older individuals with established cognitive impairment and a long duration of T2DM. Importantly, knowledge of which individuals with midlife T2DM who are at greatest risk of later cognitive decline is lacking. We examined the cross-sectional relationship between serum levels of 8 pro-inflammatory markers (IL-1, IL-6, TNF-, IL-8, MCP-1, CXCL10, IL-12p70, CRP) and performance on a detailed neuropsychological assessment battery in middle-aged adults with uncomplicated T2DM (N = 89; 52 ± 8.1 years, 47% female) and matched healthy controls (N = 50; 52 ± 8.3 years, 59% female). Linear regression was used to analyse associations between serum markers and cognitive performance in the overall cohort, followed by a T2DM*protein concentration interaction analysis to identify any T2DM-specific effects. We observed a significant T2DM-specific association between serum TNF- levels and scores on the Paired Associates Learning (PAL) task (: -3.16, SE: 1.32, p =0.01, Std. Beta: -0.94), a task with significant working memory demands previously implicated in T2DM-related cognitive dysfunction. However, this did not persist on controlling for multiple testing. We provide exploratory evidence for a significant T2DM-specific relationship between serum TNF- and memory performance. These findings require further replication and longitudinal analysis with the aim of selecting-out individuals with midlife T2DM at risk of future cognitive decline for potential preventative interventions.